(untitled) - Cummings, Joe (Australia, 1996)
Thoroughly revised and enlarged to include areas just recently opened to travelers, this guide features updated and expanded sections on accommodation and transportation options for a wide range of travel budgets and time frames. Includes 25 detailed maps of towns, cultural sites and regions, many for areas where no other maps exist. in full color.
Keywords: Burma; Guidebooks